Wow Althmania when rhetoricians (Al-Zamakhshari and Ibn Ashour - a model - . Haleel Hamdoun Al-Hashemi, Omar (Journal of College of Education, 2021)
The grammarians expressed their position on this waw as we will mention it in the preface, but it remains to be searched for the rhetoric’s position on it, especially since the waw has an important role for them, as it is based on their most important research, which is the separation and the connection. This research, the study required focusing on two important personalities in this field, namely Jarallah Abu Al-Qasim Mahmoud bin Amr bin Ahmed Al-Zamakhshari (d.538 AH) and Muhammad Al-Taher bin Ashour (d.1393 AH), because of their clear prominence and apparent distinction in This specialization, and because the first has the merit of being ahead in its development and development, and the second has taken care of it and employed it in the modern era.
Keywords: condition, selection, connotation, meanings, graphic.